Role of pharmacogenetics in personalized medicine in hepatology - Daly, Ann K. (My University, 2015)
To be described • Introduction to pharmacogenetic studies • Candidate gene case-control studies • Genome-wide association studies • Genome-wide sequencing • Exome sequencing • Whole genome sequencing • Application of pharmacogenetics to hepatology • Drug-induced liver injury • Other liver diseases
Keywords: Hígado-Enfermedades; Pharmacogenomics; Personalized medicine; Hepatology